Literature Study Analysis of The Application of Cooperative Learning Model in Futsal Game Learning on Problem Solving Abilities - Reshandi Nugraha; Alviyan Dinda Kartika; Tite Juliantine; Asep Sumpena (Journal of Physical Education For Secondary Schools, 2021)
The ability to solve problems (Problem Solving) on students is often a crucial thing in learning, to re-hone the ability of Problem Solving should a teacher must be clever in using the appropriate learning models and media. The application of the cooperative learning model is a model that emphasizes student-centeredÂ learning, the cooperative learning model will place students in situations that they have to work together to think critically in any given problem. Physical education certainly will not be separated from the material to be taught, futsal game learning material is one of thematerial that is quite systematic in supporting cooperative learning model in making learning for making effective. The application of cooperative learning model in futsal game learning can be used to lead to systematic problem situations to see the problem solving ability (Problem Solving) by researching through literature studies from journal sources found from international and national journal sites, after finding journals that are cover and relevant with the author's research, then a matrix is made which includes the name and year of the author, the results of the study, and important results that can be used by the author. After that, the results of the literature study will be analyzed by the author and adjusted to the indicators that exist in the ability of Problem Solving